Cell Culture and Tissue Engineering: Biomedical Applications - Morales-Sánchez, Johan (2019)
The Tissue Engineering Laboratory (LAINTEC) at the Biotechnology Research Center (CIB) of the Biology School at Costa Rica Institute of Technology (TEC) began in 2005, aiming towards the development of cell-based therapies for applications in regenerative medicine. Currently, LAINTEC accommodates more than a dozen multidisciplinary research projects, carried out in collaboration with other research centers from TEC as well as with other national and international universities. These investigations focus on the development and evaluation of implants, biomaterials and regenerative therapies of skin, muscle and bone tissues, including the isolation and characterization of mesenchymal stem cells from adipose tissue. In addition, cellular and tissue models are used for the evaluation of the bioactive potential of natural and synthetic agents with potential applications in biomedicine.